Development of Tourism in a Cross-Border Area on the Example of the Zachodniopomorskie Voivodship and Mecklenburg-Vorpommern - Beata Meyer; Anna Gardzińska (Barometr Regionalny, 2017)
Cross-border areas can be places of economic, social, cultural and tourism activity. Tourism development in such areas depends not only on the level of attractiveness of tourism assets and tourist infrastructure but, primarily, on the cooperation of many regional and local entities, expressed e.g. in the effective promotion of cross-border tourism products. The objective of the article is to identify determinants of tourism development and specify barriers to its development in the cross-border area of the Zachodniopomorskie Voivodship and Mecklenburg-Vorpommern. The desk research method was used for the purposes of this paper. An audit of the current tourist development of the researched area (based on data provided by the Polish and German Statistical Offices) was used to determine the area’s tourism potential. The significance of cooperation for the creation of cross-border tourist products was illustrated by case studies of selected projects. The Zachodniopomorskie Voivodship and the German Federal State of Mecklenburg-Vorpommern make up a cross-border area well placed for tourism development, on the account of numerous tourism assets, good tourism development and the activity and involvement of tourism entities in the implementation of common tourist initiatives. The obstacles in turn are mainly of an administrative and financial nature. The analyzed projects, realized in the researched area by Polish and German entities, indicate the key importance of cooperation in cross-border areas.